PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING UNTUK MENGEMBANGKAN KETERAMPILAN PROSES SAINS MATERI KLASIFIKASI TUMBUHAN - Azzahra, Alifia Salfa; Anazifa, Rizqa Devi (Jurnal Edukasi Biologi, 2025)
This research is a development research (RD) project that aims to determine the feasibility, practicality, and effectiveness of discovery learning-based Student worksheet products in developing science process skills for plant classification materials. The research design employs a one-group pre-test-post-test design. Data collection techniques use interview methods, observation, validation questionnaires for product assessment, and Pre-test and Post-test questions to measure learning outcomes. Data analysis was carried out descriptively, qualitatively and quantitatively. The results of the material expert validation obtained an average score of 3.89 with very good criteria, the results of the media expert validation obtained an average score of 3.87 with very good criteria, the results of the teacher assessment obtained an average score of 3.9 with very good criteria, the results of the student assessment showed a positive response in every aspect of the assessment. The results of the student worksheet effectiveness test, as determined by the Wilcoxon test, showed a significance value of 0.018 in the observation aspect and 0.000 in the classification, communication, and inference aspects. The N-gain of science process skills in the observation aspect falls into the medium category with a score of 0.5063, the classification aspect falls into the high category with a score of 0.7290, the communication aspect falls into the medium category with a score of 0.4362, and the inference aspect falls into the medium category with a score of 0.387. The results of the study indicate that the developed student worksheet is feasible, practical, and influential and effective in developing students' science process skills in the aspects of observation, classification, communication, and inference.